Review article: The Politics of Remembering the Suffragettes - Laura Schwartz (Revue Française de Civilisation Britannique)
This review article examines the debates and controversy surrounding the 2015 film Suffragette. It considers how historians might best engage with the politicisation of their research, and the role of the activist radical historian.